THE COMPOSITIONAL STRUCTURE OF THE WORKS OF ARTISTS WHO CREATED STILL LIFE IN PAINTING IS THEIR SCIENTIFIC ANALYSIS - Amanullyev Abdinabi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
Painting is a specialized subject like drawing, and it is one of the important subjects in the work of artists, including future painters and pedagogues. It should not be copied, but should be built on the basis of understanding the real existence, and for this, students should have acquired the most important aspects of still life drawing in the image from the first stage, and scientific interpretation and analysis will be given.